"Never known as anything but an absence, I dare not name him as god:" queer theology and the via negativa. Issue 1 (4th May 2017) - Farley, Wendy
ABSTRACT: Farley draws a parallel between the philosophical anti-essentialism of queer theory and the theological anti-essentialism of apophatic theology. She argues that absolutizing interpretations of authority conspire with dogmatic theology to strip reality of its mystery and human beings of their dignity. Greater attention to anti-essentialist theology provides one strategy toward appreciation of plurality, not least queer embodiments of the human adventure.